Glucose homoeostasis in rats exposed to acute intermittent hypoxia - Rafacho, A.; Gonçalves-Neto, L. M.; Ferreira, F. B D; Protzek, A. O P; Boschero, A. C.; Nunes, E. A.; Zoccal, Daniel Breseghello [UNESP] (Wiley, 2013)
Aim: Chronic exposure to intermittent hypoxia commonly induces the activation of sympathetic tonus and the disruption of glucose homoeostasis. However, the effects of exposure to acute intermittent hypoxia (AIH) on glucose homoeostasis are not yet fully elucidated. Herein, we evaluated parameters related to glucose metabolism in rats exposed to AIH. Methods: Male adult rats were submitted to 10 episodes of hypoxia (6% O2, for 45 s) interspersed with 5-min intervals of normoxia (21%), while the control (CTL) group was kept in normoxia. Results: Acute intermittent hypoxia rats presented higher fasting glycaemia, normal insulinaemia, increased lactataemia and similar serum lipid levels, compared to controls (n = 10, P < 0.05). Additionally, AIH rats exhibited increased glucose tolerance (GT) (n = 10, P < 0.05) and augmented insulin sensitivity (IS) (n = 10, P < 0.05). The p-Akt/Akt protein ratio was increased in the muscle, but not in the liver and adipose tissue of AIH rats (n = 6, P < 0.05). The elevated glycaemia in AIH rats was associated with a reduction in the hepatic glycogen content (n = 10, P < 0.05). Moreover, the AIH-induced increase in blood glucose concentration, as well as reduced hepatic glycogen content, was prevented by prior systemic administration of the β-adrenergic antagonist (P < 0.05). The effects of AIH on glycaemia and Akt phosphorylation were transient and not observed after 60 min. Conclusions: We suggest that AIH induces an increase in blood glucose concentration as a result of hepatic glycogenolysis recruitment through sympathetic activation. The augmentation of GT and IS might be attributed, at least in part, to increased β-adrenergic sympathetic stimulation and Akt protein activation in skeletal muscles, leading to a higher glucose availability and utilization. © 2013 Scandinavian Physiological Society.
Keywords: Blood glucose; Glucose tolerance; Insulin sensitivity; Intermittent hypoxia; Propranolol; Sympathetic activity; glucose; glycogen; insulin; lactic acid; lipid; propranolol; protein kinase B; adipose tissue; animal experiment; animal model; animal tissue; controlled study; gluconeogenesis; glucose blood level; glucose homeostasis; glucose metabolism; glucose tolerance; glycogen liver level; heart rate; hyperlipidemia; insulin blood level; insulin sensitivity; insulinemia; intermittent hypoxia; lactate blood level; lipid blood level; liver; male; mean arterial pressure; metabolic parameters; nonhuman; priority journal; protein phosphorylation; rat; skeletal muscle; sympathetic function